A Physiological Approach to Assessment and Rehabilitation of Acute Concussion in Collegiate and Professional Athletes - Ellis, Michael J.; Leddy, John; Cordingley, Dean; Willer, Barry (Frontiers in Neurology, 2018)
Sport-related concussion is an important condition that can affect collegiate and professional athletes. Expert consensus guidelines currently suggest that all athletes who sustain acute concussion be managed with a conservative approach consisting of relative rest and gradual resumption of school and sport activities with active intervention reserved for those with persistent post-concussion symptoms lasting greater than 10-14 days for adults. Unfortunately, these recommendations place little emphasis on the rapid physical deconditioning that occurs in athletes within days of exercise cessation or the pathophysiological processes responsible for acute concussion symptoms that can be successfully targeted by evidence-based rehabilitation strategies. Based on our evolving approach to patients with persistent post-concussion symptoms, we now present an updated physiological approach to the initial medical assessment, rehabilitation and multi-disciplinary management of collegiate and professional athletes with acute concussion. Utilizing the results of a careful clinical history, comprehensive physical examination and graded aerobic exercise testing, we outline how team physicians and athletic training staff can partner with multi-disciplinary experts in traumatic brain injury to develop individually tailored rehabilitation programs that target the main physiological causes of acute concussion symptoms (autonomic nervous system dysfunction/exercise intolerance, vestibulo-ocular dysfunction and cervical spine dysfunction) while maintaining the athlete’s physical fitness during the recovery period. Considerations for multi-disciplinary medical clearance of collegiate and professional athletes as well as the application of this approach to non-elite athletes are also discussed.